Formulation and Stability Tests of Hair Tonic from Oil Palm (Elaeis guineensis Jacq.) Leaves Extract and Effectiveness in Protecting Hair - Angga Cipta Narsa (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2022)
Hair loss is a condition that unavoidable process, where the hair is detached more than 100 strands per day that occurs continuously. Oil palm leaf with their compounds can be used to treat hair loss and damage. The purpose of this study was to formulate oil palm leaf extract into hair tonic preparations and evaluate the effectiveness in preventing hair damage. Hair tonic formula from oil palm leaf extract contains 96% ethanol, menthol, propylene glycol, phenoxyethanol, and aquades. The evaluation of hair tonic preparations included organoleptic, homogeneity, pH, and viscosity tests, as well as tests of antioxidant activity and effectiveness of hair tonic preparations. The results of the antioxidant activity test of oil palm leaf extract hair tonic showed the IC50 value at room temperature (25°C) indicating an average value of 37.2519±8.535 ppm, warm temperature (50°C) 40.5459±9.086 ppm, and cold temperature (4°C) 36.8257±6.928 ppm, which belongs to the category of very strong antioxidant activity, with the results of the evaluation of the oil palm leaf hair tonic slightly colored. greenish to dark green, has a distinctive menthol aroma, has a pH and viscosity that meets the requirements of a good hair tonic preparation, with pH between 3-7 and viscosity less than 5 cPs. Hair tonic preparations of oil palm leaf extract can prevent hair decolorization due to sun exposure at concentrations of 25 ppm to 200 ppm.